Identidade e subjetividade de professoras/es : sentidos do aprender e do ensinar - Scoz, Beatriz Judith Lima (2004)
This study aimed at understanding teachers construction of subjectivity and identity by drawing on the configuration of senses they convey in their learning and teaching processes within their families, neighbourhood, at school, and in formal training. Teachers perception of their own sense-conveying was also taken into account, as well as the new senses they went up building. Methodology used was the technique known as sandplay, created by jungian psychoanalyst Dora Kalff. It consists of a sandbox and miniature figures where subjects build up scenes. In this study, teachers built and described scenes of their lives and of teaching and learning situations. The use of this technique relied on the principles that ground it, on the researcher's own professional experience, and on the concepts put forth by authors like Fernando González Rey, Alicia Fernández, Sara Paín, Estelle Weinrib, and Ruth Ammann. Subjects' symbolic acts, reflexions, and emotional expressions during scene-building allowed for understanding the senses they make in their learning and teaching processes, hence their in process subjectivity and identity. Furthermore, the teachers were able to perceive themselves their situation, overcoming their fragmented understanding and redefining meanings concerning their learning and teaching processes. The use of sandplay itself has also proved educational: teachers awareness of their capacity to produce meanings, to question them, and to make new senses emerge led them to acknowledge their own thinking ability and move about through a "near-development zone", thus opening up space that favours learning. Such technique may thus be a valuable resource to overcome troubling situations in teacher training, with a view to better-quality education and teaching